2022
DOI: 10.3390/foods11142018
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Activity of Rosemary (Rosmarinus officinalis) and Garlic (Allium sativum) Essential Oils and Chipotle Pepper Oleoresin (Capsicum annum) on Beef Hamburgers

Abstract: The inclusion of natural ingredients to preserve meat and meat products has increased in recent years. This study evaluated rosemary (REO) and garlic essential oils (GEO) as well as chipotle pepper oleoresin (CPO), alone or in combination, as preservatives on beef hamburgers (BH). Six treatments were evaluated: T1 (control, without additives), T2 (GEO 1%), T3 (REO 1%), T4 (CPO 0.5%), T5 (GEO 1% + CPO 0.5%) and T6 (REO 1% + CPO 0.5%). The microbiological quality, physicochemical characteristics, sensory evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…The antifungal effectiveness of tomato plant Alternaria leaf spot disease produced by essential oil-encapsulated lipid nanoemulsions ( 126 ). Natural ingredients i.e., rosemary essential oils and GO which limited the growth of aerobic microorganisms, S. aureus, Salmonella spp., B. thermosphacta , molds and yeasts, lactic acid bacteria and coliform that act natural preserve meat and meat products ( 127 ).…”
Section: Garlic Essential Oils: Their Composition and Propertiesmentioning
confidence: 99%
“…The antifungal effectiveness of tomato plant Alternaria leaf spot disease produced by essential oil-encapsulated lipid nanoemulsions ( 126 ). Natural ingredients i.e., rosemary essential oils and GO which limited the growth of aerobic microorganisms, S. aureus, Salmonella spp., B. thermosphacta , molds and yeasts, lactic acid bacteria and coliform that act natural preserve meat and meat products ( 127 ).…”
Section: Garlic Essential Oils: Their Composition and Propertiesmentioning
confidence: 99%
“…Olivas‐Méndez et al. (2022) observed that beef hamburgers treated with chipotle pepper oleoresin reduced lipid oxidation and limited the growth of microorganisms (such as Brochothrix thermosphacta , S. aureus , Salmonella spp., lactic acid bacteria, coliforms, and molds and yeasts). Cabral et al.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Further, pepper antioxidants also form important ingredients for food preservation due to their capacity to inhibit lipid oxidation and microbial growth. Olivas-Méndez et al (2022) observed that beef hamburgers treated with chipotle pepper oleoresin reduced lipid oxidation and limited the growth of microorganisms (such as Brochothrix thermosphacta, S. aureus, Salmonella spp., lactic acid bacteria, coliforms, and molds and yeasts). Cabral et al (2021) also reported the viability of using balloon pepper (C. baccatum var.…”
Section: Novel Product Formulations Of Pepper Antioxidantsmentioning
confidence: 99%
“…For example, in a study made by Olivas-Méndez et al the use of natural antioxidants derived from rosemary ( Rosmarinus officinalis ) and garlic ( Allium sativum ) essential oils along with chipotle pepper oleoresin ( Capsicum annum ) in beef hamburgers was evaluated. The researchers found that the addition of the aforementioned extracts improved the microbiological quality and inhibited the lipid oxidation of the beef hamburgers [ 59 ]. Similar research was carried out by Mostafa et al in which the addition of antioxidants derived from green coffee was compared with ascorbic acid in beef meatballs.…”
Section: Antioxidants Used In the Meat Industry—current Overviewmentioning
confidence: 99%